Method for preparing multi-component alloy catalyst
By coating and washing the carbon composite support with cationic polymer, the metal load of the multi-component alloy catalyst is improved, the problems of process complexity and platinum usage in the prior art are solved, and efficient catalytic activity is achieved and durability while reducing the amount of platinum used.
Patent Information
- Application Number
- CN201910893423.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-04-02
- Filing Date
- 2019-09-20
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2039-09-20
AI Technical Summary
Existing multicomponent alloy catalysts are complex when loading high-volume metal catalysts, and it is difficult to reach metal loads of 60% by weight or more, which limits the performance and durability of the catalyst, especially the high price and limited platinum in platinum-containing catalysts. Reserve issues.
The carbon composite is used as the support, and the carbon support is coated with cationic polymer, and the platinum and transition metal are supported. After washing and drying, the loading of the catalytic metal is significantly increased to 60% by weight or more.
A high loading of multi-component alloy catalyst is achieved, which improves catalytic activity and durability, while reducing the amount of platinum used and simplifying the process flow.
Smart Images

Figure CN111769295B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a method for preparing a multi-component alloy catalyst on which a catalytic metal is supported. Background Art
[0002] Nanosized metal particles have been studied in various technological fields over the past decades due to their unique properties. In particular, platinum has been used in various catalytic reactions including fuel cells due to its excellent surface activity, but its use is limited due to its high price and limited remaining discoverable reserves.
[0003] Therefore, in order to solve the above problems, a catalyst containing a reduced amount of platinum is required. To achieve this purpose, a platinum-based multi-component alloy catalyst containing an alloy of platinum and a transition metal has been developed, so that the platinum content can be reduced. However, this catalyst is synthesized in a complicated process and it is difficult to load an amount of catalytic metal equivalent to that of a commercially available platinum catalyst, which limits the catalyst performance and durability.
[0004] In addition, the platinum catalyst must be subjected to a complicated process in which conditions such as pH are controlled for a long time in order to increase the amount of metal supported thereon. In the case of an alloy catalyst containing three or more components, its synthesis process is more complicated, and because it is difficult or impossible to prepare a catalyst capable of supporting a high amount of metal of about 60% by weight or more, a catalyst supporting a low amount of metal of 20% to 40% by weight is synthesized and used.
[0005] The above information disclosed in this Background section is provided only for enhancement of understanding of the background of the disclosed embodiments and therefore it may contain information that does not form the prior art that is already known to a person of ordinary skill in the art. Summary of the invention
[0006] The disclosed embodiments are presented to solve the above-mentioned problems associated with the prior art.
[0007] An object of the present application is to provide a method for preparing a multi-component alloy catalyst containing three or more components, the method being capable of increasing the amount of metal loaded on the multi-component alloy catalyst and solving the process complexity.
[0008] Another object of the present application is to provide a method for preparing a multi-component alloy catalyst, which can reduce the amount of platinum used and provide excellent catalytic activity.
[0009] The purpose of the present application is not limited to those mentioned above. The purpose of the present application can be clearly understood through the following description and claims.
[0010] In one aspect, the present application provides a method for preparing a multi-component alloy catalyst. The method comprises: preparing a carbon composite having a carbon support coated with a cationic polymer; loading a catalytic metal containing at least two metal elements on the carbon composite to prepare an alloy catalyst precursor; and washing the alloy catalyst precursor to remove the cationic polymer.
[0011] The method may further include drying the product free of the cationic polymer under an inert gas atmosphere after removing the cationic polymer.
[0012] The cationic polymer may be selected from polyethyleneimine (PEI), polyethyleneimine ethoxylate (PEIE), poly-L-lysine (PLL) and combinations thereof.
[0013] The carbon composite may be prepared by adding the carbon support and the cationic polymer to a solvent at a weight ratio of 1:0.5 to 1:2, followed by stirring.
[0014] The catalytic metal may include platinum (Pt) and at least one transition metal selected from copper (Cu), iron (Fe), nickel (Ni), cobalt (Co), manganese (Mn), chromium (Cr) and combinations thereof.
[0015] The catalytic metal may include platinum (Pt), copper (Cu), and at least one transition metal selected from iron (Fe), nickel (Ni), cobalt (Co), manganese (Mn), chromium (Cr), and combinations thereof.
[0016] The preparation of the alloy catalyst precursor may include adding a transition metal precursor to a dispersion in which the carbon composite is dispersed, adding a platinum precursor to the dispersion containing the transition metal precursor, and reacting the dispersion containing the platinum precursor.
[0017] The reaction may be performed at a temperature of 150° C. to 250° C. for 10 to 20 hours.
[0018] The alloy catalyst precursor may be washed with distilled water at 60°C to 70°C to remove the cationic polymer.
[0019] The multi-component alloy catalyst may support the catalytic metal in an amount of 60 wt % or more.
[0020] In another aspect, the present application provides a method for manufacturing a membrane electrode assembly. The method includes: preparing a multi-component alloy catalyst; coating a release paper with the multi-component alloy catalyst to prepare a catalyst layer; and transferring the catalyst layer to an electrolyte membrane. The method for preparing a multi-component alloy catalyst can be accomplished by the method disclosed and described herein.
[0021] Other aspects and embodiments of the present application are discussed herein. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] The above and other features of the present application are described in detail with reference to certain embodiments of the present application shown in the accompanying drawings, which are given herein by way of illustration only and therefore do not limit the present application, and in which:
[0023] Figure 1 A flow chart showing a method for preparing a multi-component alloy catalyst according to the present application;
[0024] Figure 2 A carbon composite is schematically shown;
[0025] Figure 3 A carbon catalyst precursor is schematically shown;
[0026] Figure 4 A multi-component alloy catalyst is shown;
[0027] Figure 5A shows the measurement results of the amount of catalytic metal supported on the alloy catalyst in Example 1;
[0028] Figure 5B shows the measurement results of the amount of catalytic metal supported on the alloy catalyst in Example 2;
[0029] Figure 5C shows the measurement results of the amount of catalytic metal supported on the alloy catalyst in Comparative Example 1;
[0030] Figure 5D shows the measurement results of the amount of catalytic metal supported on the alloy catalyst in Comparative Example 2;
[0031] Fig. 6A Showing the transmission electron microscope (TEM) analysis results of the alloy catalyst according to Example 1;
[0032] Figure 6B Showing the transmission electron microscope (TEM) analysis results of the alloy catalyst according to Example 2;
[0033] Figure 6C Shows the transmission electron microscope (TEM) analysis results of the alloy catalyst according to Comparative Example 1;
[0034] Fig.6D Shows the transmission electron microscope (TEM) analysis results of the alloy catalyst according to Comparative Example 2;
[0035] Fig. 7A The measurement results of the polarization curves of the oxygen reduction reaction (ORR) in Example 1 and Comparative Example 1 are shown;
[0036] Figure 7B The measurement results of the polarization curves of the electrochemical oxygen reduction reaction (ORR) in Example 2 and Comparative Example 2 are shown;
[0037] Fig. 8A shows the electrochemical surface areas in Example 1 and Comparative Example 1; and
[0038] Figure 8B The electrochemical surface areas in Example 2 and Comparative Example 2 are shown. DETAILED DESCRIPTION
[0039] The above objects and other objects, features and advantages will be clearly understood by the following embodiments with reference to the accompanying drawings. However, the present application is not limited to these embodiments, but can be embodied in different forms. These embodiments are disclosed only to provide a comprehensive and complete understanding of the disclosed context and to enable those of ordinary skill in the art to fully understand the technical ideas of the present application.
[0040] Throughout the description of the accompanying drawings, the same reference numerals refer to the same elements / elements. In the accompanying drawings, for clarity, the size of the structure is enlarged. It should be understood that, although the terms "first", "second", etc. can be used to describe each element / element in this article, these elements / elements should not be interpreted as being limited by these terms, and these terms are only used to distinguish one element / element from another element / element. For example, within the scope defined by the present application, the "first" element / element can be referred to as the "second" element / element, and similarly, the "second" element / element can be referred to as the "first" element / element. Unless the context clearly indicates otherwise, the singular form is also intended to include the plural form.
[0041] It should be further understood that when used in this specification, the terms "include / comprise" and / or "have" illustrate the presence of the described features, values, steps, operations, elements, components or combinations thereof, but do not exclude the presence or addition of one or more other features, values, steps, operations, elements, components or combinations thereof. In addition, it should be understood that when an element such as a layer, film, region or substrate is referred to as being "above" another element, it can be directly above the other element, or there can be intermediate elements. It should also be understood that when an element such as a layer, film, region or substrate is referred to as being "below" another element, it can be directly below the other element, or there can be intermediate elements.
[0042] Unless the context clearly indicates otherwise, all numbers, values and / or expressions representing components, reaction conditions, polymer compositions and mixture amounts used in this specification are approximate values, i.e., the approximate values reflect, among other things, the various measurement uncertainties that naturally exist when obtaining these values. For this reason, it should be understood that in all cases, the term "about" should be understood to modify all numbers, values and / or expressions. In addition, when numerical ranges are disclosed in the specification, these ranges are continuous and include all numbers from the minimum to the maximum, including the maximum value in each range, unless otherwise limited. In addition, when a range refers to an integer, it includes all integers from the minimum to the maximum, including the maximum value in the range, unless otherwise limited.
[0043] Figure 1 A flow chart showing a method for preparing a multi-component alloy catalyst according to the present application is shown. Figure 1 The method may include: a step S10 of preparing a carbon composite having a carbon support coated with a cationic polymer; a step S20 of loading a catalytic metal containing two or more metal elements on the carbon composite to prepare an alloy catalyst precursor; a step S30 of washing the alloy catalyst precursor to remove the cationic polymer; and a step S40 of drying the product free of the cationic polymer under an inert gas atmosphere.
[0044] The term "multi-component alloy catalyst" used herein means a catalyst in which a catalytic metal containing an alloy of two or more metal elements is supported on a carrier.
[0045] The step S10 of preparing the carbon composite may include: injecting the carbon carrier and the cationic polymer into a solvent, and then stirring, so that the carbon carrier is coated with the cationic polymer.
[0046] Figure 2 The carbon composite 10 is schematically shown. Figure 2 The carbon composite 10 may include: a carbon carrier 11 and a cationic polymer 12 coated on the carbon carrier 11 .
[0047] Any carbon support 11 known to those skilled in the art may be used as the carbon support 11 without limitation.
[0048] The average particle size, specific surface area, and shape of the carbon support 11 may fall within a general range known to a person of ordinary skill in the art to which the present application belongs. Figures 2 to 4 The carbon support 11 is shown in the form of particles, but the shape of the carbon support 11 is not limited thereto.
[0049] The carbon support 11 may be pretreated with an acid, an alkali, or the like, and the surface of the carbon support 11 may be modified by oxygen plasma treatment or the like.
[0050] The term "cationic polymer" used herein means a polymer having a cationic functional group in its main chain or side chain.
[0051] In some cases, the cationic polymer 12 may include a member selected from the group consisting of polyethyleneimine (PEI), polyethyleneimine ethoxylate (PEIE), poly-L-lysine (poly-L-lysine , PLL) and any combination thereof.
[0052] The cationic polymer 12 may be coated on the entire surface or a portion of the surface of the carbon support 11 . Figure 2 and Figure 3 It is shown that the cationic polymer 12 is coated on the entire surface of the carbon support 11, but the present application is not limited thereto.
[0053] The carbon composite 10 can be prepared by adding the carbon support 11 and the cationic polymer 12 to a solvent at a weight ratio of 1:0.5 to 1:2, followed by stirring. When the weight ratio of the cationic polymer 12 to the carbon support 11 is less than 0.5, the cationic polymer 12 cannot be fully coated on the surface of the carbon support 11, and the effect of increasing the amount of the supported catalytic metal will be insufficient; and when the weight ratio exceeds 2, it may be difficult to remove the cationic polymer 12 in the subsequent step.
[0054] The solvent may be an alcohol, such as isopropyl alcohol, but is not limited thereto.
[0055] The carbon composite 10 can be prepared by stirring under appropriate time, temperature and speed conditions. However, the stirring conditions of the carbon support 11 and the cationic polymer 12 are not limited thereto.
[0056] The step S20 of supporting a catalytic metal containing two or more metal elements on the carbon composite 10 to prepare an alloy catalyst precursor may include adding the catalytic metal precursor to a dispersion in which the carbon composite 10 is dispersed, and may include reacting the components under specific conditions to prepare the alloy catalyst precursor.
[0057] Figure 3 The carbon catalyst precursor 1 is schematically shown. Figure 3 The carbon catalyst precursor 1 may include: a carbon composite 10 including a carbon support 11 and a cationic polymer 12 , and a catalytic metal supported on the carbon composite 10 .
[0058] The catalytic metal 20 may include two or more metal elements and may be an alloy of platinum (Pt) and a transition metal. The catalytic metal 20 may be a two-component system, a three-component system, a four-component system, or a system having more components.
[0059] In some cases, the catalytic metal 20 may include platinum (Pt) and at least one transition metal selected from copper (Cu), iron (Fe), nickel (Ni), cobalt (Co), manganese (Mn), chromium (Cr), and combinations thereof.
[0060] In some other cases, the catalytic metal 20 may include: platinum (Pt); copper (Cu); and at least one transition metal selected from iron (Fe), nickel (Ni), cobalt (Co), manganese (Mn), chromium (Cr), and combinations thereof.
[0061] In some cases, the catalytic metal 20 may be Pt-Cu-Fe or Pt-Cu-Ni.
[0062] The step S20 of preparing the alloy catalyst precursor 1 may include: adding a transition metal precursor to a dispersion in which the carbon composite 10 is dispersed; adding a platinum precursor to the dispersion containing the transition metal precursor; and reacting the obtained dispersion.
[0063] When the number of transition metals alloyed with platinum is two or more, two or more transition metal precursors may be added simultaneously or separately. In some cases, the transition metal precursors are added separately. For example, after adding one transition metal precursor followed by stirring, another transition metal precursor may be added and stirred.
[0064] Regarding the types of transition metal precursors and platinum precursors, any precursor known to a person of ordinary skill in the art to which the present application pertains, such as metal acetylacetonate, may be used without limitation.
[0065] The amount of transition metal precursor added, the amount of platinum precursor added, and the weight ratio of transition metal precursor to platinum precursor are not particularly limited. For example, the transition metal precursor and platinum precursor may be added in excess to maximize the amount of catalytic metal 20 supported.
[0066] The alloy catalyst precursor 1 can be prepared by adding a transition metal precursor and a platinum precursor to a dispersion, and then reacting the dispersion in a high pressure and high temperature reactor at a temperature of 150° C. to 250° C. and a stirring speed of 300 to 400 RPM for a reaction time of 10 to 20 hours.
[0067] Then, as described in the related step S30 , the alloy catalyst precursor 1 is washed to remove the cationic polymer 12 , thereby obtaining the multi-component alloy catalyst 2 . Figure 4 A multi-component alloy catalyst 2 is shown.
[0068] The alloy catalyst precursor 1 may be washed with distilled water at 60° C. to 70° C. and filtered using a filter to remove the cationic polymer 12. The number of washing times is not particularly limited and may be appropriately controlled.
[0069] As the cationic polymer 12 is removed, the multi-component alloy catalyst 2 in which the catalytic metal 20 is supported on the carbon support 11 can be obtained.
[0070] Then, as described in the related step S40, the multi-component alloy catalyst 2 may be dried at room temperature and under an inert gas atmosphere (eg, argon or nitrogen).
[0071] Compared with conventional multi-component alloy catalysts, the amount of catalytic metal 20 supported on the multi-component alloy catalyst 2 obtained by the above method is significantly improved. For example, the multi-component alloy catalyst 2 may contain: the catalytic metal 20 in an amount of 60 wt% or more, 60 wt% to 90 wt%, or 60 wt% to 80 wt%, based on the total weight of the carbon support 11 and the catalytic metal 20 (i.e., the total weight of the catalyst).
[0072] The multi-component alloy catalyst 2 prepared by the above method can be used as a catalyst layer of a fuel cell. For example, the multi-component alloy catalyst 2 can be coated on a release paper to prepare a catalyst layer, and then the catalyst layer can be transferred to an electrolyte membrane to prepare a membrane-electrode assembly.
[0073] Hereinafter, the present application may be described in more detail with reference to examples. However, the following examples are provided only for illustrating the present application and should not be construed as limiting the scope of the present application.
[0074] Example 1
[0075] As described in the related step S10, polyethyleneimine ethoxylate (PEIE) and the carbon support are added to isopropanol in a weight ratio of 1:1, and then stirred. After about 12 hours, the solvent is removed, the product is washed with ethanol, and then dried in an oven at about 80° C. for about 12 hours to obtain a carbon composite.
[0076] As described in the related step S20, the carbon composite is added to a mixed solvent of dimethylformamide (DMF) and ethylene glycol (EG) and dispersed using an ultrasonic disperser. Then, potassium hydroxide is added thereto and stirred for 1 hour to obtain a dispersion. A predetermined amount of Cu (C 5 H 7 O 2 ) 2 (Copper acetylacetonate) was added to the dispersion, followed by stirring for about 30 minutes. Then, a predetermined amount of Fe(C 5 H 7 O 2 ) 3(ferric acetylacetonate), the dispersion was stirred for about 1 hour, and then a predetermined amount of dimethylformamide (DMF) was added thereto. Finally, Pt(C) dissolved in a mixed solvent of dimethylformamide (DMF) and ethylene glycol (EG) was added. 5 H 7 O 2 ) 2 (platinum acetylacetonate) solution. The mixture was reacted for about 15 hours in a high-pressure and high-temperature reactor while being stirred at about 350 RPM while maintaining a temperature of about 170° C., thereby obtaining an alloy catalyst precursor.
[0077] As described in the related step S30, the alloy catalyst precursor is washed several times with distilled water at 60° C. to 70° C. using a Teflon filter to remove polyethyleneimine ethoxylate (PEIE), thereby obtaining a multi-component alloy catalyst comprising a Pt-Cu-Fe catalytic metal supported on a carbon carrier.
[0078] As described in the related step S40, the multi-component alloy catalyst is dried at room temperature and under an inert gas atmosphere.
[0079] Example 2
[0080] The multi-component alloy catalyst was prepared in the same manner as in Example 1, except that Ni(C 5 H 7 O 2 ) 3 (nickel acetylacetonate) instead of Fe(C 5 H 7 O 2 ) 3 (Ferric acetylacetonate). The multi-component alloy catalyst according to Example 2 comprises Pt-Cu-Ni catalytic metal supported on a carbon support.
[0081] Comparative Example 1
[0082] The multi-component alloy catalyst was prepared by directly supporting the catalytic metal on the carbon support without coating the carbon support with a cationic polymer. The details of the preparation method are as follows.
[0083] The carbon support was added to a mixed solvent of dimethylformamide (DMF) and ethylene glycol (EG), and the carbon support was dispersed therein using an ultrasonic disperser. Potassium hydroxide was then added thereto, and the mixture was stirred for 1 hour to obtain a dispersion. A predetermined amount of Cu (C 5 H 7 O 2 ) 2 (Copper acetylacetonate) was added to the dispersion, followed by stirring for about 30 minutes. Then, a predetermined amount of Fe(C 5 H7 O 2 ) 3 (ferric acetylacetonate), and after stirring the dispersion for about 1 hour, dimethylformamide (DMF) was added thereto. Finally, Pt(C) dissolved in a mixed solvent of dimethylformamide (DMF) and ethylene glycol (EG) was added. 5 H 7 O 2 ) 2 (platinum acetylacetonate) solution. The mixture was reacted for about 15 hours in a high pressure and high temperature reactor while being stirred at about 350 RPM while maintaining a temperature of about 170° C., thereby obtaining a multi-component alloy catalyst comprising a Pt-Cu-Fe catalytic metal supported on a carbon carrier.
[0084] The multi-component alloy catalyst was dried at room temperature under an inert gas atmosphere.
[0085] Comparative Example 2
[0086] A multi-component alloy catalyst was prepared in the same manner as in Comparative Example 1, except that Ni(C 5 H 7 O 2 ) 3 (nickel acetylacetonate) instead of Fe(C 5 H 7 O 2 ) 3 (Ferric acetylacetonate). The multi-component alloy catalyst according to Comparative Example 2 includes a Pt-Cu-Ni catalytic metal supported on a carbon support.
[0087] Experimental Example 1 - Measurement of the amount of supported catalytic metal
[0088] The amount of catalytic metal loaded on the alloy catalyst according to Example 1, Example 2, Comparative Example 1 and Comparative Example 2 was measured by thermogravimetric analysis (TGA). During the thermogravimetric analysis, the temperature of the catalyst was raised to 800°C at a rate of 10°C / min under an oxygen atmosphere, during which the carbon support was pyrolyzed and removed. Finally, only the catalytic metal remained. As a result, the amount of catalytic metal loaded on the alloy catalyst can be measured by comparing the amount of the remaining catalytic metal with the total amount of the catalytic metal initially loaded.
[0089] The results are shown in FIG. 5A to FIG. 5D For example, Figure 5A The results of measuring the amount of catalytic metal supported on the alloy catalyst in Example 1 are shown. Figure 5B The results of measuring the amount of catalytic metal supported on the alloy catalyst in Example 2 are shown. Figure 5C The results of measuring the amount of catalytic metal supported on the alloy catalyst in Comparative Example 1 are shown. Figure 5D The measurement results of the amount of the catalytic metal supported on the alloy catalyst in Comparative Example 2 are shown.
[0090] from Figure 5A It can be seen that, regarding the multi-component alloy catalyst according to Example 1 of the present application, the amount of Pt-Cu-Fe loaded is about 60 wt %. On the other hand, regarding the multi-component alloy catalyst prepared without using a cationic polymer in Comparative Example 1, the amount of Pt-Cu-Fe loaded is only about 39 wt %.
[0091] At the same time, from Figure 5C It can be seen that the amount of Pt-Cu-Ni supported on the multi-component alloy catalyst according to Example 2 of the present application is about 60 wt %. On the other hand, the amount of Pt-Cu-Ni supported on the multi-component alloy catalyst prepared without using a cationic polymer in Comparative Example 2 is only about 36 wt %.
[0092] These results indicate that the amount of catalytic metals supported on the multi-component alloy catalyst obtained by the preparation method according to the present application has been increased to a level that was not possible in the prior art.
[0093] Experimental Example 2- Transmission Electron Microscope (TEM) Analysis
[0094] The alloy catalysts according to Example 1, Example 2, Comparative Example 1 and Comparative Example 2 were subjected to transmission electron microscopy (TEM) analysis. The results are shown in FIG. 6A to FIG. 6D middle. Fig. 6A 1 shows the results of transmission electron microscopy (TEM) analysis of the alloy catalyst according to Example 1, Figure 6B : shows the transmission electron microscope (TEM) analysis results of the alloy catalyst according to Example 2, Figure 6C The transmission electron microscope (TEM) analysis results of the alloy catalyst according to Comparative Example 1 are shown. Fig.6D Transmission electron microscope (TEM) analysis results of the alloy catalyst according to Comparative Example 2 are shown.
[0095] By comparison Fig. 6A and Figure 6C It can be seen that the amount of catalytic metal supported on the multi-component alloy catalyst according to Example 1 is significantly greater than that of Comparative Example 1.
[0096] Similarly, by comparing Figure 6B and Fig.6D It can be seen that the amount of catalytic metal loaded on the multi-component alloy catalyst according to Example 2 is significantly greater than that of Comparative Example 2.
[0097] Experimental Example 3-Evaluation of electrochemical characteristics
[0098] In order to evaluate the electrochemical oxygen reduction reaction (ORR) activity and electrochemical surface area (ECSA), a rotating disk electrode (RDE) was used to obtain the polarization curves and electrochemical surface area of the oxygen reduction reaction.
[0099] The area of the rotating disk electrode is 19.6mm 2 , and the method of loading the synthesized catalyst onto the electrode surface is as follows.
[0100] A powdered catalyst is dispersed in alcohol, an ionomer is added thereto to prepare a catalyst ink, and then a predetermined amount of the catalyst ink is dropped on a rotating disk electrode and dried to evaporate the alcohol, so that only a thin film type of catalyst remains on the rotating disk electrode.
[0101] The electrochemical properties were evaluated using a three-electrode system. SCE electrode was used as the reference electrode and platinum wire was used as the counter electrode. All analyses were performed at room temperature.
[0102] The experimental conditions used to obtain the ORR polarization curves were as follows. The electrolyte solution was saturated with oxygen and then oxygen was continuously supplied during the analysis. The scan rate was 5 mV / sec, and the scan rate range was 0.05 V to 1.0 V (relative to RHE). Finally, the rotation speed of the electrode was maintained at 1600 RPM.
[0103] The results are shown in Fig. 7A and Figure 7B middle. Fig. 7A The results of Example 1 and Comparative Example 1 are shown. Figure 7B The results of Example 2 and Comparative Example 2 are shown. As the half-wave potential of the polarization curve increases, the activity of the oxygen reduction reaction increases. The half-wave potential value in Examples 1 and 2 is about 0.94V, while the half-wave potential value in Comparative Examples 1 and 2 is about 0.90V. Therefore, it can be seen that the activity for the oxygen reduction reaction of Examples 1 and 2 according to the present application is superior to that in Comparative Examples 1 and 2.
[0104] Fig. 8A The electrochemical surface areas of Example 1 and Comparative Example 1 are shown. Figure 8B The electrochemical surface areas of Example 2 and Comparative Example 2 are shown. Referring to these figures, Example 1 and Example 2 show larger electrochemical surface areas than Comparative Example 1 and Comparative Example 2, respectively. This indicates that the multi-component alloy catalysts according to Examples 1 and 2 have increased electrochemical surface areas compared to Comparative Examples 1 and 2.
[0105] It is obvious from the foregoing that according to the method for preparing a multi-component alloy catalyst of the present application, an alloy catalyst having a much higher amount of supported catalytic metals can be obtained compared to a conventional multi-component alloy catalyst.
[0106] According to the method for preparing a multi-component alloy catalyst of the present application, an alloy catalyst can be obtained in a relatively simple manner compared to conventional preparation methods.
[0107] According to the method for preparing a multi-component alloy catalyst of the present application, an alloy catalyst with improved catalytic activity and reduced platinum dosage can be obtained.
[0108] The effects of the present application are not limited to those described above. It should be understood that the effects of the embodiments of the present application include all effects that can be inferred from the above description.
[0109] The present application includes a plurality of embodiments described in detail. However, it should be understood by those skilled in the art that changes can be made in these embodiments without departing from the principles and spirit of the present application, and the scope of the present application is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a multi-component alloy catalyst, the method comprising: preparing a carbon composite having a carbon support coated with a cationic polymer; A catalytic metal containing at least two metal elements is supported on a carbon composite to prepare an alloy catalyst precursor; as well as The alloy catalyst precursor is washed to remove the cationic polymer by using a filter.
2. A method for preparing a multi-component alloy catalyst, the method comprising: preparing a carbon composite having a carbon support coated with a cationic polymer; A catalytic metal containing at least two metal elements is supported on a carbon composite to prepare an alloy catalyst precursor; as well as washing the alloy catalyst precursor to remove the cationic polymer, Here, the alloy catalyst precursor is washed with distilled water at 60° C. to 70° C. to remove the cationic polymer.
3. The method for preparing a multi-component alloy catalyst according to claim 1 or 2, further comprising: After the cationic polymer is removed, the product free of cationic polymer is dried under an inert gas atmosphere.
4. The method for preparing a multi-component alloy catalyst according to claim 1 or 2, wherein: The cationic polymer is selected from polyethyleneimine, polyethyleneimine ethoxylate, poly-L-lysine and combinations thereof.
5. The method for preparing a multi-component alloy catalyst according to claim 1 or 2, wherein: The carbon composite is prepared by adding the carbon support and the cationic polymer to a solvent at a weight ratio of 1:0.5 to 1:2, followed by stirring.
6. The method for preparing a multi-component alloy catalyst according to claim 1 or 2, wherein: The catalytic metal comprises: Platinum; and At least one transition metal selected from the group consisting of copper, iron, nickel, cobalt, manganese, chromium and combinations thereof.
7. The method for preparing a multi-component alloy catalyst according to claim 1 or 2, wherein: The catalytic metal comprises: platinum; Copper; and At least one transition metal selected from the group consisting of iron, nickel, cobalt, manganese, chromium and combinations thereof.
8. The method for preparing a multi-component alloy catalyst according to claim 1 or 2, wherein: The preparation of the alloy catalyst precursor comprises: adding a transition metal precursor to the dispersion in which the carbon composite is dispersed; adding a platinum precursor to a dispersion containing a transition metal precursor; and A dispersion containing a platinum precursor is reacted.
9. The method for preparing a multi-component alloy catalyst according to claim 8, wherein: The reaction is performed at a temperature of 150° C. to 250° C. for 10 to 20 hours.
10. The method for preparing a multi-component alloy catalyst according to claim 1, wherein: The alloy catalyst precursor was washed with distilled water at 60°C to 70°C to remove the cationic polymer.
11. The method for preparing a multi-component alloy catalyst according to claim 1 or 2, wherein: The multi-component alloy catalyst supports a catalytic metal in an amount of 60 wt % or more.
12. A method for manufacturing a membrane-electrode assembly, the method comprising: A multi-component alloy catalyst is prepared by the method according to claim 1 or 2; Coating a release paper with a multi-component alloy catalyst to prepare a catalyst layer; as well as The catalyst layer is transferred onto the electrolyte membrane.
Citation Information
Patent Citations
Electrode catalyst for fuel cell and the manufacturing method of the same
KR1020160007888A
Production Method of Electrode Applied Spray Coating on Porous Release Paper
KR1020170130774A
